1997
DOI: 10.1021/jf960789q
|View full text |Cite
|
Sign up to set email alerts
|

Heat-Induced Aggregation of β-Lactoglobulin:  Role of the Free Thiol Group and Disulfide Bonds

Abstract: The heat-induced aggregation of bovine β-lactoglobulin, dispersed in water at neutral pH and in different concentrations (10, 30, or 50 g of dry matter/L), was studied at 65 °C, and the results are related to a kinetic model. Native PAGE and SDS−PAGE analysis under nonreducing and reducing conditions showed that on heating disulfide-linked aggregates were formed and that the average size of these aggregates increased with increasing initial β-lactoglobulin concentration. In the presence of the thiol-blocking a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

30
293
2
3

Year Published

1999
1999
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 365 publications
(328 citation statements)
references
References 29 publications
(45 reference statements)
30
293
2
3
Order By: Relevance
“…This heat-induced distribution of the two protein species was accounted for by their interaction through hydrophobic bonding and thiol/disulfide interchanges to form heat-induced serum whey protein/κ-casein aggregates, in agreement with previous reports [3-6, 26, 32]. The analysis of the serum phase of reconstituted skim milk heated at pH values ranging from 6.6 to 8.1 suggested that smaller but more numerous heat-induced aggregates were present in the serum phase as heat-treatment pH increased, in agreement with previous studies [12,24,32]. The analysis of the micellar phase of the same milk samples did not, however, indicate that less whey protein/κ-casein aggregates could be bound to the casein micelles as heat-treatment pH increased.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This heat-induced distribution of the two protein species was accounted for by their interaction through hydrophobic bonding and thiol/disulfide interchanges to form heat-induced serum whey protein/κ-casein aggregates, in agreement with previous reports [3-6, 26, 32]. The analysis of the serum phase of reconstituted skim milk heated at pH values ranging from 6.6 to 8.1 suggested that smaller but more numerous heat-induced aggregates were present in the serum phase as heat-treatment pH increased, in agreement with previous studies [12,24,32]. The analysis of the micellar phase of the same milk samples did not, however, indicate that less whey protein/κ-casein aggregates could be bound to the casein micelles as heat-treatment pH increased.…”
Section: Discussionsupporting
confidence: 92%
“…Upon heating at pH > 6.7, heat-induced milk protein aggregates are reported to be smaller, more numerous [24] and with a higher proportion of disulphide bonds compared with hydrophobic interactions [12,13]. Upon heating milk at pH > 6.9, the proportion of heat-induced whey protein/κ-casein aggregates found in the serum phase is increased, while casein micelles are depleted in κ-casein as a result of their interaction with denatured whey protein and dissociation [2-5, 26-28, 32].…”
Section: Introductionmentioning
confidence: 99%
“…The rate of aggregation of heat-stressed beta-lactoglobulin increased with increasing pH, which is consistent with the pH dependence of disulphide bond cleavage [23,26] . Law et al [23] found that the rate of denaturation of beta-lactoglobulin was increased at higher pH values.…”
Section: Discussionsupporting
confidence: 78%
“…Beta-lactoglobulin aggregates via a combination of disulphide bond exchange (which leads to polymerization) and a nucleation-dependent mechanism due to hydrophobic association [26,27] . Mainly heatinduced aggregation of beta-lactoglobulin occurs through the formation of a dimer-monomer transition state of the protein.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the presence of these groups has substantial impact on the aggregation and gelation behavior of a wide variety of proteins which has been confirmed by many researchers (Arntfield et al, 1991;Broersen et al, 2006;Graña-Montes et al, 2011;Hayakawa & Nakai, 1985;Hoffmann & van Mil, 1997;Margoshes, 1990;Mine, 1992;Sawyer, 1968;Shimada & Cheftel, 1989). A variety of modifications can be performed targeting sulfhydryl groups, which are part of the cysteine residues.…”
Section: Chemical-reactive Groupsmentioning
confidence: 92%